Placenta-Derived Cells for Acute Brain Injury - Francesca Pischiutta; Eliana Sammali; Ornella Parolini; Hilary V. O. Carswell; Elisa R. Zanier (Cell Transplantation, 2018)
Acute brain injury resulting from ischemic/hemorrhagic or traumatic damage is one of the leading causes of mortality and disability worldwide and is a significant burden to society. Neuroprotective options to counteract brain damage are very limited in stroke and traumatic brain injury (TBI). Given the multifaceted nature of acute brain injury and damage progression, several therapeutic targets may need to be addressed simultaneously to interfere with the evolution of the injury and improve the patient’s outcome. Stem cells are ideal candidates since they act on various mechanisms of protection and repair, improving structural and functional outcomes after experimental stroke or TBI. Stem cells isolated from placenta offer advantages due to their early embryonic origin, ease of procurement, and ethical acceptance. We analyzed the evidence for the beneficial effects of placenta-derived stem cells in acute brain injury, with the focus on experimental studies of TBI and stroke, the engineering strategies pursued to foster cell potential, and characterization of the bioactive molecules secreted by placental cells, known as their secretome, as an alternative cell-free strategy. Results from the clinical application of placenta-derived stem cells for acute brain injury and ongoing clinical trials are summarily discussed.